ANALISIS PELAKSANAAN KURIKULUM MERDEKA PADA PEMBELAJARAN SENI RUPA KELAS VIII DI SMP NEGERI 30 PADANG - Fina Febriana Pardanti; Suib Awrus (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research was motivated by teachers not yet properly understanding how to apply the independent curriculum in learning arts and culture (fine arts). This research aims, firstly, to describe the implementation of the independent curriculum in class VIII arts and culture subjects at SMP Negeri 30 Padang, secondly to describe the obstacles in implementing the independent curriculum in class VIII arts and culture (fine arts) subjects at SMP Negeri 30 Padang, thirdly to describe the efforts made in implementing the independent curriculum in class VIII arts and culture subjects at SMP Negeri 30 Padang. This research method uses a qualitative descriptive research method. In this research, the informants requested in this research were the deputy principal in the field of curriculum, arts and culture teachers and class VIII students. The data analysis technique in this research uses the Miles and Huberman model of qualitative data analysis techniques, namely data reduction, data presentation and data verification and conclusions. The technique for testing the validity of the data used is the source triangulation technique. The results of this research show that in implementing the independent curriculum it is related to arts and culture learning (fine arts), character surveys and environmental surveys in its application in the implementation process. Meanwhile, other independent learning policy programs such as Modules have been implemented. Teachers in implementing modules that are in accordance with the independent curriculum can create their own without being separated from the Merdeka curriculum platform. From the independent learning platform provided by the government and the implementation of the independent curriculum policy, the school follows the system in the independent curriculum and before implementing it the school holds a meeting. However, due to obstacles in implementing the independent curriculum related to learning arts and culture (fine arts), character surveys and environmental surveys have not yet achieved Learning Achievements (CP). In carrying out the implementation of modules in learning activities by arts and culture teachers, it is felt that there is a lack of variety in the learning media used, the difficulty of creating modules in determining learning media and the difficulty of accessing the internet and obstacles in implementing the independent learning policy program, teachers are reluctant to open independent learning platforms, the difficulty in accessing the internet and student learning outcomes have not been achieved. Meanwhile, in efforts to implement an independent curriculum in arts and culture (fine arts) subjects, arts and culture teachers use Jigsaw learning strategies and use learning media, namely Audio-Visual learning media, and the efforts made to implement an independent curriculum are related to the independent learning policy program. In its implementation, art and culture teachers and school officials  still find obstacles in its implementation.